Exploring online learning: Virtual teaching quality, student satisfaction, and academic performance among nursing students in Peru – a cross-sectional study - Sharif, Loujain S.; Fernandez-Delgado, Jhan CM.; Aguilar-Altamirano , Erick E.; Ramírez-Ramírez, Wildoro; Mahsoon, Alaa; Banakhar, Maram; Fernández-Sanchez, Higinio (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Virtual teaching has become an essential component of nursing education today, but its impact on practical courses remains unexplored. There is a need to understand how the quality of virtual teaching influences both academic performance and student satisfaction. Objective: This study aims to explore how nursing students’ satisfaction and academic performance in practical courses relate to the quality of virtual teaching in a Peruvian university in 2023. Methods: A descriptive cross-sectional correlational study was conducted by surveying 125 nursing students in northern Peru from March to May 2023. The data were collected using the Online Education Scale and Academic Satisfaction Scale. Academic performance was assessed through documentary analysis of the students’ general averages, and Kendall’s tau-b test was used to assess the relationship. Additionally, Pearson’s Chi-square test and both bivariate and multivariate logistic regression analyses were conducted to obtain more precise relationships. Results: The study found that 54.4% of nursing students rated virtual teaching quality as low, with the same percentage reporting low satisfaction and 59.2% having low academic performance. Virtual teaching quality was positively correlated with satisfaction (τb = 0.415, p <0.01) and negatively with academic performance (τb = -0.176, p = 0.043). Pearson’s Chi-square and logistic regression showed significant relationships in several virtual teaching dimensions. Virtual collaborative teaching and development of virtual capabilities were rated low by 72.8% and 60.8% of students, respectively. Both had significant odds ratios (COR: 4.1, AOR: 3.8, p = 0.012 and COR: 3.8, AOR: 3.5, p = 0.010). Virtual resources and accompaniment showed moderate ratings, with significant results for virtual resources (COR: 1.5, AOR: 1.3, p <0.001) and virtual accompaniment (COR: 1.2, AOR: 1.0, p = 0.040). Conclusion: This study revealed that poor-quality virtual teaching negatively impacted nursing students in Peru, leading to reduced satisfaction and academic performance. The positive correlation between teaching quality and satisfaction suggests that improving virtual teaching could enhance student satisfaction. However, the negative correlation with academic performance highlights challenges in adapting practical nursing education to virtual formats. Improving virtual methodologies and exploring innovative strategies, such as hybrid learning models, are essential for improving outcomes in nursing education.